Colloquial Vietnamese : - Vương, Đức Tuấn (Routledge, 2007)
Colloquial Vietnameseis a practical course in everyday written and spoken Greek, requiring no prior knowledge of the language. It is ideal for anyone seeking to develop a sound command of contemporary Vietnamese. For self-study or class use. This paperbackin the Colloquial Language Learning Series is available individually here or as part of a cassette pack. To purchase the bookandthe cassettes, please refer to the cassette pack listing for this language.